Kajian Implementasi Sistem Informasi Manajemen Dalam Meningkatkan Efektivitas Pengelolaan Organisasi - Cindy Aryani; Amelia Kartika; Muhhammad Rizal (Perkumpulan Konsultan Manajemen Pendidikan Indonesia (PKMPI), 2026)
The rapid advancement of information technology has encouraged organizations to adopt Management Information Systems (MIS) as a strategic tool to enhance organizational management effectiveness. MIS plays a crucial role in providing accurate, relevant, and timely information to support planning, organizing, controlling, and decision-making processes. This article aims to examine the implementation of Management Information Systems in improving organizational management effectiveness through a literature review approach. The research method employed is a literature review by analyzing various scientific sources, including books, national journals, and international journals published between 2021 and 2025. The findings indicate that the implementation of MIS contributes positively to organizational management effectiveness by improving information quality, operational efficiency, interdepartmental coordination, employee productivity, and decision-making quality. Furthermore, the success of MIS implementation is influenced by management support, human resource readiness, technological infrastructure, and an organizational culture that supports digital transformation. The study concludes that MIS serves as a strategic instrument that enables organizations to achieve their objectives more effectively and efficiently amid increasingly complex environmental dynamics. Therefore, organizations should optimize the implementation of MIS to enhance organizational performance and maintain sustainable competitiveness.